Corporate Value: Are Investors Evaluating Environmental Performance and Eco-Efficiency Alongside Profitability? - Caecilia Widi Pratiwi; Mochamad Ilham Fauzi; Emmy Indrayani (Universitas Gunadarma, 2024)
Corporate value refers to the evaluation investors place on a company's success and performance, which is reflected in its stock market price. This study seeks to analyze the impact of Environmental Performance, Profitability, and Eco-Efficiency on Corporate Value. The independent variables include environmental performance, measured by adherence to standards, profitability assessed through return on assets, and eco-efficiency represented by ISO-14001 certifications. The research utilizes secondary data from the annual financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. A purposive sampling technique was employed based on specific criteria, resulting in a sample of 10 companies. Data analysis was conducted using multiple linear regression analysis with SPSS version 25. The findings indicate that Environmental Performance and Eco-Efficiency do not significantly affect Corporate Value, whereas profitability does have an impact.